Scaling of Drizzle Virga Depth With Cloud Thickness for Marine Stratocumulus Clouds - Fan Yang; Edward P. Luke; Pavlos Kollias; Alex B. Kostinski; Andrew M. Vogelmann (Geophysical Research Letters)
Abstract Drizzle is frequently observed in marine stratocumulus clouds and plays a crucial role in cloud lifetime and the radiation budget. Most drizzling stratocumulus clouds form drizzle virga below cloud base, where subcloud scavenging and evaporative cooling are important. We use unique ground‐based cloud radar observations (1) to examine the statistical properties of drizzle frequency and virga depth and (2) to test a simple analytical relationship derived between drizzle virga thickness (Hv) and cloud thickness (Hc). Observations show that 83% of marine stratocumulus clouds are drizzling although only 31% generate surface precipitation. The analytical expression for Hv is derived as a function of Hc and subcloud relative humidity considering in‐cloud accretion and subcloud evaporation of drizzle drops. The derived third‐order power law relationship, Hv∼Hc3, shows good agreement with long‐term observational data. Our formula provides a simple parameterization for drizzle virga of stratocumulus clouds suitable for use in models.